The history of embalming in the era of anatomists of the XV-XVIII centuries - Chilingaridi, Svetlana Ninelievna; Shemyakov, Sergey Evgenievich; Milyukov, Vladimir Yefimovich; Nikiforova, Elena Evgenevna; Sharifova, Kheyalya Murshud Kizi; Sharifov, Elshan Rovshan Oglu; Nguyen, Cao Cuong (International Journal of Human Anatomy, 2023)
A historical review traces embalming practices and their role in anatomical study between the 15th and 18th centuries, connecting technique evolution to scientific milestones and ethics.